2019
DOI: 10.1002/jcb.28909
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 promotes hypoxia‐induced renal tubular epithelial apoptosis through downregulating miR‐27a‐3p

Abstract: Acute kidney injury (AKI) is a common kidney disorder that affects public health and the incidence of AKI. Sepsis, acute ischemia or hypoxia is the main reason for the occurrence of AKI. Recently, noncoding RNA that include microRNA and long noncoding RNA (lncRNAs) were reported to play important roles in AKI as well as have the potential to serve as a biomarker or therapeutic target for the development of the diagnostic and prognostic strategies of AKI. In the current study, we aimed to investigate the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…A previous study suggested that lncRNA NEAT1 contributed to sepsis-triggered AKI via repressing miR-204 and activating the NF-κB pathway [19]. Besides, Jiang et al revealed that NEAT1 aggravated ischemiainduced injury via functioning as a ceRNA of miR-27a-3p [9]. Similar to previous research studies, the NEAT1 expression was dramatically increased in patients with sepsis in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A previous study suggested that lncRNA NEAT1 contributed to sepsis-triggered AKI via repressing miR-204 and activating the NF-κB pathway [19]. Besides, Jiang et al revealed that NEAT1 aggravated ischemiainduced injury via functioning as a ceRNA of miR-27a-3p [9]. Similar to previous research studies, the NEAT1 expression was dramatically increased in patients with sepsis in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 66%
“…LncRNA nuclear-enriched abundant transcript 1 (NEAT1) has been reported to play a crucial role in the innate immune response. Previous research has corroborated that NEAT1 aggravated ischemiainduced AKI via directly targeting miR-27a-3p [9]. Moreover, NEAT1 promoted sepsis-induced brain injury in mice by mediating the nuclear factor (NF)-κB pathway [10].…”
Section: Introductionmentioning
confidence: 92%
“…37 And in sepsisinduced organ injury, interaction between lncRNA and miRNA also plays an important role. For instance, lncRNA NEAT1 promotes hypoxia-induced renal tubular epithelial apoptosis via downregulating miR-27a-3p 38 ; lncRNA MALAT1 aggravates cardiac inflammation and dysfunction in sepsis by regulating miR-125b and p38 MAPK/NF-κB pathway. 39 Our data indicated that CYTOR could inhibit miR-24 expression by binding with it to attenuate the injury of cardiomyocytes during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al underscored that hypoxia induced NEAT1 expression in hepatocellular carcinoma (HCC), and NEAT1 silencing repressed HCC cell migration and invasion under hypoxia [28]. Jiang et al highlighted that NEAT1 accelerated hypoxia-induced renal tubular epithelial apoptosis via down-regulating miR-27a-3p [29].…”
Section: Discussionmentioning
confidence: 99%